2020
DOI: 10.1002/cncr.33062
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of therapeutic strategy for p16‐positive oropharyngeal squamous cell carcinoma: Multi‐institutional observational study based on the national Head and Neck Cancer Registry of Japan

Abstract: Background Although the American Joint Committee on Cancer TNM classification has been amended to include human papillomavirus (HPV)–related oropharyngeal squamous cell carcinoma (OPSCC) as an independent entity, to the authors' knowledge the optimized de‐escalating treatment modality has not been established to date. Methods The authors conducted a retrospective, nationwide, observational study in patients with HPV‐related OPSCC who were treated from 2011 to 2014 in Japan to determine the best treatment modal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…TNM-8 uses p16 positivity as a surrogate of HPV infection similar to this study. Although some have reported better differentiation of OS according to stages by TNM-8 than by 7th edition TNM classi cation (7)(8)(9), there are also reports indicating that prognoses according to the stages are inadequately differentiated, especially between stage II and III by using TNM-8 for p16positive OPSCC (10)(11)(12). Current study showed the stages de ned by TNM-8 were inadequate in differentiating OS and DSS.…”
Section: Discussionmentioning
confidence: 55%
“…TNM-8 uses p16 positivity as a surrogate of HPV infection similar to this study. Although some have reported better differentiation of OS according to stages by TNM-8 than by 7th edition TNM classi cation (7)(8)(9), there are also reports indicating that prognoses according to the stages are inadequately differentiated, especially between stage II and III by using TNM-8 for p16positive OPSCC (10)(11)(12). Current study showed the stages de ned by TNM-8 were inadequate in differentiating OS and DSS.…”
Section: Discussionmentioning
confidence: 55%
“…Rather, transoral surgery or radiotherapy could be sufficient to curb disease progression and offer an elevated quality of life. In advanced stages of HPV-associated oropharyngeal squamous cell carcinoma (OPSCC), induction chemotherapy and chemoradiotherapy with cisplatin tends to be the choice of treatment [ 218 ]. A Japanese team showed that the HPV-associated OPSCC of TNM stage 1/2, radiotherapy alone, or concurrent chemotherapy resulted in 69.5% five-year recurrence-free survival and overall survival rates [ 218 , 219 ].…”
Section: Treatment Regimensmentioning
confidence: 99%
“…Consequently, there has been a worldwide attempt to reduce the treatment intensity for HPVrelated OPSqCC (Saito et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in 2017, the American Joint Committee on Cancer TNM classification specified HPV-related OPSqCC as a separate entity and set a lenient classification (i.e., downstaging) to this malignancy ( O'Sullivan et al 2016 ; Machczyński et al 2020 ). Consequently, there has been a worldwide attempt to reduce the treatment intensity for HPV-related OPSqCC ( Saito et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%